Redescription of the tadpole of Odontophrynus carvalhoi Savage and Cei, 1965 (Anura, Odontophrynidae) with comments on the geographical distribution of the species - Santos-Silva, Danusy Lopes; Andrade, Sheila P.; Rocha, Cezar Filho; Maciel, Natan M.; Caramaschi, Ulisses; Vaz-Silva, Wilian (Zootaxa, 2017)
The genus Odontophrynus is distributed throughout the Neotropics being represented by eleven species (Frost 2017). Recently, Caramaschi & Napoli (2012) presented a taxonomic revision of the species belonging to the Odontophrynus cultripes species group including the redescription of O. carvalhoi together with natural history attributes, advertisement call description and geographic distribution remarks.